The Impact of the First Goal in the Final Result of the Futsal Match - Werlayne Stuart Soares Leite (The Society of Aging and Physical Activity (SAPA), 2013)
Among the many technical and tactical aspects of the behavior of players, the goals are the most studied. The goal is the key to success for teams and its analysis in all matches of a major futsal tournament (World Cup) that allows multiple assessments. The aim of this study was to analyze the impact of the first goal for the final result in the futsal match, identifying the team that scored the first goal of the match and the final result obtained by this team: win, draw or lose. We analyzed all the matches (n=306), in all the 7 Futsal World Cups (1989 to 2012) organized by Fédération Internationale de Football Association - FIFA. Data were obtained from the database on the site of the FIFA, through overviews of the official matches. Quantitative data were collected, in relation to the time that the goals were scored in the course of the matches. The results showed a significant effect (F = 133.12, p = 0.001) of first goals on final results of maches (win, draw, defeat); so that, there are significant deference between win matches with darw and defeat matches [both (p = 0.001)]. It is concluded that, the team that scored the first goal of the match presents a high probability of getting the winning.